Biomarkers to predict the success of treatment with the intravitreal 0.19 mg fluocinolone acetonide implant in uveitic macular edema - Kessler, Lucy Joanne; Łabuz, Grzegorz; Auffarth, Gerd U.; Khoramnia, Ramin (Pharmaceutics, 2022)
To predict the need for additional local corticosteroids after receiving the 0.19 mg fluocinolone acetonide (FAc) implant in patients with macular edema secondary to non-infectious uveitis previously treated with local peribulbar corticosteroids. The number of corticosteroids required prior FAc, visual acuity, central retinal thickness, ellipsoid zone reflectivity ratio (EZR), and choroidal vascularity index (CVI) were compared between patients who did and did not require additional corticosteroids after FAc implantation. Pearson’s correlation coefficient (R) between putative predictors and the number of adjunctive corticosteroids after FAc implantation were measured; significant candidates were included in a generalized regression model. Patients who required additional corticosteroids after FAc had higher CVI and central retinal thickness as well as worse EZR at subsequent visits (p < 0.05). The number of corticosteroids required prior to FAc implantation (R: 0.49), CVI change from baseline to 6 months (R: −0.41), and central retinal thickness at baseline (R: −0.36) correlated to the number of additional corticosteroids (all p < 0.05). A higher number of corticosteroids per year before FAc implantation was predictive for an increase in corticosteroids required after FAc (odds ratio = 2.65), while a decrease in CVI from baseline to 6 months was inversely correlated (odds ratio = 0.82). Our results suggest that the more corticosteroids prior to FAc and the greater the short-term CVI reducing effect, the less is the chance to get additional corticosteroids after FAc.